2015
DOI: 10.1021/acs.nanolett.5b02010
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Organic Nanocrystals with Strong Nonlinear Optical Response

Abstract: Facile molecular self-assembly affords a new family of organic nanocrystals that, unintuitively, exhibit a significant nonlinear optical response (second harmonic generation, SHG) despite the relatively small molecular dipole moment of the constituent molecules. The nanocrystals are self-assembled in aqueous media from simple monosubstituted perylenediimide (PDI) molecular building blocks. Control over the crystal dimensions can be achieved via modification of the assembly conditions. The combination of a simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…[13] Polymer growth is favored by the strong mutual reinforcement between these two linkages,w hich allows the self-assembly of functional and persistent structures. Controlling the structure and conjugation length of the organic portion of metallopolymers is crucial to optimizing their electronic properties.P olymer length also determines the morphology of the material, impacting device performance,scalability of preparation, and solution processability, [15] which are essential considerations for bespoke device fabrication. Controlling the structure and conjugation length of the organic portion of metallopolymers is crucial to optimizing their electronic properties.P olymer length also determines the morphology of the material, impacting device performance,scalability of preparation, and solution processability, [15] which are essential considerations for bespoke device fabrication.…”
mentioning
confidence: 99%
“…[13] Polymer growth is favored by the strong mutual reinforcement between these two linkages,w hich allows the self-assembly of functional and persistent structures. Controlling the structure and conjugation length of the organic portion of metallopolymers is crucial to optimizing their electronic properties.P olymer length also determines the morphology of the material, impacting device performance,scalability of preparation, and solution processability, [15] which are essential considerations for bespoke device fabrication. Controlling the structure and conjugation length of the organic portion of metallopolymers is crucial to optimizing their electronic properties.P olymer length also determines the morphology of the material, impacting device performance,scalability of preparation, and solution processability, [15] which are essential considerations for bespoke device fabrication.…”
mentioning
confidence: 99%
“…Organic solvents were of spectroscopic or HPLC grade, dried over molecular sieves (3 Å), and filtered over 0.2‐μm PTFE syringe filters prior to use. Syntheses of the PDI derivatives followed literature procedures …”
Section: Methodsmentioning
confidence: 99%
“…Hence, organic nanocrystals (ONCs), whose solubility and morphology are difficult to control, have not been employed in polymer/nanohybrids. Aromatic ONCs can be robust and exhibit useful photonic properties, [11][12][13][14][15][16] yet their fabrication is based mostly on empirical methods. 17 Addressing this challenge, we have recently demonstrated that rational design based on hydrophobicity tuning can be applied to control structure and morphology, resulting in soluble and tunable ONCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalization with amine and alcohol through The mononitration of PDI 1 is more selective, owing to the electron-withdrawing inductive and mesomeric effects of the nitro group, which sufficiently deactivates the PDI core towards the second electrophilic substitution. The reaction was initially performed by Langhals and colleagues, who attained 98% yield using a solution of N 2 O 4 gas (prepared by strong heating of Pb(NO 3 ) 2 ) and methanesulfonic acid (CH 3 SO 3 H) as the catalyst in CH 2 Cl 2 [38,39], and this was achieved more easily using nitric acid in the presence of cerium (IV) ammonium nitrate (CAN) in CH 2 Cl 2 with nearly quantitative yields [30,31,[40][41][42][43][44][45][46]. The kinetics of the reaction were reported to be higher using a mixture of HNO 3 and H 2 SO 4 [47][48][49].…”
Section: Nucleophilic Substitution Of the Nitro Groupmentioning
confidence: 99%